Synthesis and Thermal Adsorption Characteristics of Silver-Based Hybrid Nanocomposites for Automotive Friction Material Application - R. Venkatesh; P. Sakthivel; M. Vivekanandan; C. Ramesh Kannan; J. Phani Krishna; S. Dhanabalan; T. Thirugnanasambandham; Manaye Majora (Adsorption Science & Technology)
Advances in friction materials are imposed on developing multiceramic reinforced hybrid nanocomposites with superior tribomechanical properties. The silver-based matrix metals are gained significance in various applications like bearing, ratchet, and electrical contacts due to their high frictional resistance and good thermal and chemical stability compared to traditional metals. The present research is to develop silver-based hybrid nanocomposites containing alumina (Al2O3) and silicon carbide (SiC) nanoparticles of 50 nm mixing with the ratio of 0 wt% Al2O3/0 wt% SiC, 5 wt% Al2O3/0 wt% SiC, and 5 wt% Al2O3/5 wt% SiC via the semisolid vacuum stir-cast technique. The vacuum technology minimizes casting defects and increases composite properties. The casted composite samples are subjected to study the effect of reinforcement on thermal adsorption, conductivity, diffusivity, and frictional resistance. The composite containing 5 wt% Al2O3np/5 wt% SiCnp is to find optimum thermal and frictional behaviour. The thermal adsorption and frictional resistance are increased by 30% and 27% compared to unreinforced cast silver. The Ag/5 wt% Al2O3np/5 wt% SiCnp hybrid nanocomposite is recommended for automotive friction-bearing applications.